Techno-economic analysis of 1,3-propanediol, sorbitol, itaconic acid, and xylooligosaccharides production from sugarcane-based feedstocks - Van Heerden, Cara (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.